Live-seminar: Securing food in a warmer and more extreme world - CGIAR Research Program on Climate Change, Agriculture and Food Security (2013)
On Friday 25 October Dr Bruce Campbell, CCAFS Director, gave presentation on 'Securing food in a warmer and more extreme world' to the Swedish University of Agriculture (SUL). This is the recording of that seminar. Get the presentation: http://ow.ly/qdmMx